SA-13 Scabiosis (Notoedres cati) in Cat - Miyayu Soneta Sofyan; M Herry Susanto; M Ulin Nuha (Hemera Zoa, 2018)
Feline scabies also referred as Notedric mange (Notoedres cati). This diseases is highly contagious skin disease. The symptom of this disease is a severe and relentless itch include a skin rash composed of small red bumps and blisters on the specific areas such as face, ear, neck, paws pads and spreading to the rest of the body. This disease was  very contagious for cats and kittens which can opportunistically infest other mammals, including human (Griffin et al., 1993).Notoedres mites are closely related to Sarcoptic mites of dogs and thus the two infestations have some similarity. Both the conditions typically begin with itchy crusts and scales on the ear margins. The Notoedric mange progresses to involve the face and ultimately covers the entire body, if the skin disease was ignored. (Scott et al.,2001). Three cats in the present study had mange lesions covering the entire body.The characteristic itching and hair loss pattern was often all that was needed to diagnose Notoedric mange in the cat (Griffin et al., 1993). Scraping of the crusty skin examined, revealed all stages of Notoedres cati mite (from ova to adult) in the present study and confirmed the diagnosis. Notoedres mites are smaller than Sarcoptes, have ‘thumb print’-like dorsal striations, shorter limb stalks and a dorsal anus compared with the terminal anus, dorsal pegs and spines seen on Sarcoptes species (Scott et al. 2001). The mites were identified as per the reports of Walker (1994) based on their shape and the presence of dorsal anus, which distinctly differentiated the Notoedres cati from Sarcoptes sp. The present report describes case of notoedric mange I two cats and successful management with ivermectin therapy.